MENJAWAB TUDUHAN IDEOLOGISASI DALAM TAFSIR AHKAM: Telaah atas Kitab AsbÄb IkhtilÄf al-MufasirÄ«n fÄ« TafsÄ«r á¾¹yÄt al-Aá¸¥kÄm - Abdul Wadud Kasful Humam (AL ITQAN: Jurnal Studi Al-Qur'an, 2020)
This article examines the answer of Abdul Ilāh Ḥūri to the accusation of ideologization in tafsīr ayāt aḥkām (Qur’anic exegesis on the legal verses) through  his work Asbāb Ikhtilāf al-Mufassirīn fī Tafsīr Ᾱyāt al-Aḥkām. The tendency to ideologize these schools of tafsīr can be understood not only because of the writer's background as a demonstrative school activist, but other factors are also very influential on the resulting tafsīr ayāt aḥkām products, such as: differences in using the rules of al-'ibrah bi 'umūm al-lafẓi lā bi khuṣūṣ al-sabab or vice versa, differences in choosing qirā'at, differences in interpreting siyāq (context) or in his term that is called mā fī al-Qur'ān and mā ḥaula al-Qur'ān.